2015
DOI: 10.1002/2014jg002691
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a reconstruction from in situ measurements: 1. Method description

Abstract: Understanding the development of primary production is essential for projections of the global carbon cycle in the context of climate change. A chlorophyll a hindcast that serves as a primary production indicator was obtained by fitting in situ measurements of nitrate, chlorophyll a, and temperature. The resulting fitting functions were adapted to a modeled temperature field. The method was applied to observations from the Madeira Basin, in the northeastern part of the oligotrophic North Atlantic Subtropical G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Fründt et al [] showed with a shorter time series from 1980 to 2008, by applying EOF analysis, a correlation between the DCM and the NAO on a period of roughly 5 years. Application of the wavelet coherence between the time coefficient of the first EOF (Figure b) and the NAO showed that the relationship between NAO and the DCM found between 1980 and 2008 was less contributed to the long‐term variability of the DCM since this relationship had not been established before the 1980s (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fründt et al [] showed with a shorter time series from 1980 to 2008, by applying EOF analysis, a correlation between the DCM and the NAO on a period of roughly 5 years. Application of the wavelet coherence between the time coefficient of the first EOF (Figure b) and the NAO showed that the relationship between NAO and the DCM found between 1980 and 2008 was less contributed to the long‐term variability of the DCM since this relationship had not been established before the 1980s (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of the correlation coefficients ρ between the NAO and the time coefficient of the first EOF showed significant results at a time lag of 0 years ( ρ =0.17, p =0.041) and of 9 years ( ρ =0.21, p =0.016, Figure b) which corresponded to the phase difference as seen in the wavelet coherence. The direct correlation with NAO, i.e., no time lag, was diminished compared to the value found in Fründt et al [] when only the last 28 years were regarded, because a continuous correlation over the entire length was not found. The time lag of 9 years might be related to the transmission of NAO‐induced oceanic signals by slow Rossby waves with speeds of around 1 cm s −1 as reported by Cipollini et al [].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depth and magnitude of the SCM affect the vertical distribution of zooplankton and fish (Pannard et al, 2015). Therefore, the SCM can play a key role in determining the structure and function of aquatic ecosystems (Frundt et al, 2015;Williamson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%